Does gene deletion of AMPA GluA1 phenocopy features of schizoaffective disorder? - Fitzgerald, P; Barkus, C; Feyder, M; Wiedholz, L; Chen, Y; Karlsson, R; Machado-Vieira, R; Graybeal, C; Sharp, T; Zarate, C; Harvey-White, J; Du, J; et al. (2010)
Glutamatergic dysfunction is strongly implicated in schizophrenia and mood disorders. GluA1 knockout (KO) mice display schizophrenia- and depression-related abnormalities. Here, we asked whether GluA1 KO show mania-related abnormalities. KO were tested for behavior in approach/avoid conflict tests, responses to repeated forced swim exposure, and locomotor responses under stress and after psychostimulant treatment. The effects of rapid dopamine depletion and treatment with lithium or a GSK-3β inhibitor (SB216763) on KO locomotor hyperactivity were tested. Results showed that KO exhibited novelty- and stress-induced locomotor hyperactivity, reduced forced swim immobility and alterations in approach/avoid conflict tests. Psychostimulant treatment and dopamine depletion exacerbated KO locomotor hyperactivity. Lithium, but not SB216763, treatment normalized KO anxiety-related behavior and partially reversed hyperlocomotor behavior, and also reversed elevated prefrontal cortex levels of phospho-MARCKS and phospho-neuromodulin. Collectively, these findings demonstrate mania-related abnormalities in GluA1 KO and, combined with previous findings, suggest this mutant may provide a novel model of features of schizoaffective disorder.